Unraveling the mystery of canopy dieback caused by citrus disease Huanglongbing and its link to hypoxia stress - Shahzad, Faisal; Tang, Lisa; Vashisth, Tripti (Frontiers in Plant Science, 2023)
Devastating citrus disease Huanglongbing (HLB) is without existing cures. Herein, we present results demonstrating the possible mechanisms (hypoxia stress) behind HLB-triggered shoot dieback by comparing the transcriptomes, hormone profiles, and key enzyme activities in buds of severely and mildly symptomatic ‘Hamlin’ sweet orange (Citrus sinensis). Within six months (October – May) in field conditions, severe trees had 23% bud dieback, greater than mild trees (11%), with a concomitant reduction in canopy density. In February, differentially expressed genes (DEGs) associated with responses to osmotic stress, low oxygen levels, and cell death were upregulated, with those for photosynthesis and cell cycle downregulated in severe versus mild trees. For severe trees, not only were the key markers for hypoxia, including anaerobic fermentation, reactive oxygen species (ROS) production, and lipid oxidation, transcriptionally upregulated, but also alcohol dehydrogenase activity was significantly greater compared to mild trees, indicating a link between bud dieback and hypoxia. Tricarboxylic acid cycle revival, given the upregulation of glutamate dehydrogenase and alanine aminotransferase DEGs, suggests that ROS may also be generated during hypoxia-reoxygenation. Greater (hormonal) ratios of abscisic acid to cytokinins and jasmonates and upregulated DEGs encoding NADPH oxidases in severe versus mild trees indicate additional ROS production under limited oxygen availability due to stomata closure. Altogether, our results provided evidence that as HLB progresses, excessive ROS produced in response to hypoxia and during hypoxia-reoxygenation likely intensify the oxidative stress in buds leading to cell death, contributing to marked bud and shoot dieback and decline of the severely symptomatic sweet orange trees.